Learning from museums - Falk, John H. (John Howard) 1948-; Dierking, Lynn D. (Rowman & Littlefield, 2018)
"In the second edition of their 2000 book, John H. Falk and Lynn D. Dierking offer an updated version of the Contextual Model of Learning, as well as present the latest advances in museum research, theory, and practice in order to provide readers an inside view of how and why people learn from their museum experiences"